Bone mineral density and turnover response to GLP-1 receptor agonists in older adults with overweight/obesity and prediabetes/type 2 diabetes: a 20-week pilot trial post hoc analysis - Dinkla, Lauren; Beavers, Kristen M.; Robbins, Ronna; Akpalu, Dela; Wherry, Sarah J.; Miller, Gary; Beavers, Daniel P.; Espinoza, Sara; Trejo, Jonathan; Stepanenko, Allison; Cortes, Tiffany M. (Frontiers in Aging, 2025)
The purpose of this exploratory post hoc analysis was to study the impact of semaglutide on measures of bone health in older adults. Data were collected from a 20-week pilot trial (NCT05786521), which randomized 20 older adults (72.7 ± 4.8 years of age, 50% women, 45% Hispanic) living with prediabetes/diabetes (hemoglobin A1C 5.7%–7.5%) and overweight/obesity [body mass index (BMI): 32.9 ± 4.0 kg/m2] to 1.0 mg/weekly semaglutide + lifestyle counseling (n = 10) or lifestyle counseling alone (n = 10). The total body weight, bone mineral density (BMD), and bone turnover markers (BTMs) [C-terminal telopeptide of type 1 collagen (CTX) and procollagen type I N-propeptide (P1NP)] were measured at baseline and 20 weeks. Twenty-week weight loss was greater in the semaglutide + lifestyle counseling group than in lifestyle counseling alone (−5.3% vs. −0.89%; p < 0.01). No significant differences in whole-body BMD (p = 0.77) or BTMs (CTX: p = 0.56, P1NP: p = 0.78) were observed between groups over time. In this 20-week pilot trial, we did not find evidence to suggest that weight loss achieved with semaglutide was associated with change in BMD or BTMs in older adults. Notably, the observed differences showed consistently lower BMD and higher bone turnover at follow-up in the semaglutide + lifestyle group than in the lifestyle alone. Additional work in this area is warranted to further evaluate the effect of glucagon-like peptide-1 receptor agonist (GLP1Ra) use on skeletal health outcomes in older adults, given the pilot nature of the trial, the small degree of weight loss achieved, and the well-described association between weight loss and fracture risk.